TAHAPAN PERKEMBANGAN MORAL SANTRI MAHASISWA MENURUT LAWRENCE KOHLBERG - Anata Ikrommullah (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2015)
Abstrak: this research was conducted with the aim to describe: (1) the stages of moral development of students grade students Pesantren Mahasiswa Al-Hikam Malang, (2) the analysis of the stages of moral development of santri mahasiswa Pesantren Mahasiswa Al-Hikam Malang.In this descriptive study, researchers sought to describe how the results of the stages of moral development santri mahasiswa of class IV. Through this type of research data that has been collected in the form of the results of the questionnaire moral dilemmas (DIT) Jamest Rest systematically arranged, accurate and factual.Research findings indicate that (1) the highest level of students are students in Law And Order level of 62.5%, (2) as much as 22.2% in stage Nice Girl and Good Boy, (3) the third largest stages are stages Social Contract which amounted to 12.5%, (4) Stages of Jamest Rest which serves as an internal check that Meaningless much as 2.5%.Keywords: stages of moral development, santri mahasiswa, Lawrence Kohlberg.